ANALYSIS OF IMPACT OF MINERAL AND COAL COMMODITIESÃâÃâ BALANCE OF TRADE TO BALANCE OF PAYMENTS AND GROSS DOMESTIC PRODUCTS OF INDONESIA - FAUZI (NIM : 22108034), AHMAD
The economic growth of Indonesia is supported by export of natural resources. The export policies were reformed in order to reduce dependences in export of gas and petroleum and to increase in export of non gas and petroleum commodities. After economic crisis in 1997, the surplus of Indonesia‟s BOP has been dominated by surplus in BOT of goods. In 1989, the optimum BOT of goods and services was 7.05 times of the actual BOT of goods and services, the optimum of Indonesia‟s BOP was 39.7 times of the actual Indonesia‟s BOP, and the optimum GDP was 1.14 times of the actual GDP. The optimum BOT of goods and services could be reached if the output of petroleum and gas mining sector were IDR 104.9 trillion; output of petroleum and gas refinery sector were IDR 14.7 trillion; output of mineral manufactured sector were IDR 61.3 trillion; output of transportation and communication sector were IDR 11.7 trillion; output of services sector were IDR 73.8 trillion. In 2008, the optimum BOT of goods and services was 10.13 times of the actual BOT of goods and services, the optimum of Indonesia‟s BOP was -27.9 times of the actual Indonesia‟s BOP, and the optimum GDP was 1.11 times of the actual GDP. These optimum conditions could be reached if output of petroleum and gas mining sector were IDR 2,615 trillion; output of petroleum and gas refinery sector were IDR 571.3 trillion; output of mineral manufactured sector were IDR 3,537 trillion; output of transportation and communication sector were IDR 236 trillion; output of services sector were IDR 1,806 trillion. Meanwhile the equation of Indonesia‟s BOP (Z) linear regression concerning BOT of goods and services (E-M)bj is = -639.79(1010) + 0.389 (E-M)bj and its coefficient correlation (r) is 0.653. The equation of Indonesia‟s GDP (Y) linear regression concerning BOT of goods and services (E-M)bj is Ŷ = 491,347.2(1010)+ 14.347 (E-M)bj and its coefficient correlation (r) is 0.689. The equation of Indonesia‟s BOP (Z) linear regression concerning BOT of coal and minerals (E-M)min is = 748.155(1010) + 0.711 (E-M)min and its coefficient correlation (r) is 0.693. And the equation of Indonesia‟s GDP (Y) linear regression concerning coal and minerals (E-M)min is Ŷ = 51,512.99(1010) + 32.367 (E-M)min and its coefficient correlation (r) is 0.935. In 2008, the commodities which had surplus in their BOT and higher than 1.00 in their TOT were copper, gold, stone, and gas. The commodities which had surplus in their BOT and lower than 1.00 in their TOT were tin, nickel, and coal. The commodities which had deficit in their BOT and lower than 1.00 in their TOT were iron and steel, aluminium, other metallic minerals, and non-metallic minerals. The commodity which had deficit in its BOT and higher than 1.00 in its TOT was petroleum. With the results that in order to achieve the optimum of BOT of goods and services, commodities export should be in end use form and the output of services sectors also should be increased. Exploration of natural resources should be increased on coal, metallic minerals, industrial minerals, some petroleum and gas basins that less been explored